Learning to coexist with wildfire - Moritz, Max A.; Batllori, Enric; Bradstock, Ross A.; Gill, A. Malcolm; Handmer, John; Hessburg, Paul F.; Leonard, Justin; McCaffrey, Sarah; Odion, Dennis C.; Schoennagel, Tania; Syphard, Alexandra D. (Nature (London), 2014)
The impacts of escalating wildfire in many regions — the lives and homes lost, the expense of suppression and the damage to ecosystem services — necessitate a more sustainable coexistence with wildfire. Climate change and continued development on fire-prone landscapes will only compound current problems. Emerging strategies for managing ecosystems and mitigating risks to human communities provide some hope, although greater recognition of their inherent variation and links is crucial. Without a more integrated framework, fire will never operate as a natural ecosystem process, and the impact on society will continue to grow. A more coordinated approach to risk management and land-use planning in these coupled systems is needed.